1954
DOI: 10.1149/1.2781218
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Oxidation of High Purity Nickel

Abstract: The effect of time, temperature, and surface pretreatment on rate of oxidation of high purity nickel is studied for the temperature range of 400~176 using a vacuum microbalance technique. The data are compared to previous studies in the literature and with other metals. Oxidation data are interpreted in terms of the parabolic rate law and classical theory of diffusion.Large deviations from the parabolic rate law are found to occur during the initial stages of reaction and smaller deviations over long periods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
22
2

Year Published

1954
1954
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(29 citation statements)
references
References 8 publications
5
22
2
Order By: Relevance
“…P resent ed as an American Society of Lubrication En gineers paper at the Lu brication Con ference held in Pittsbu rgh, Pennsylvania, Octob er [16][17][18]1962.…”
Section: Introductionmentioning
confidence: 99%
“…P resent ed as an American Society of Lubrication En gineers paper at the Lu brication Con ference held in Pittsbu rgh, Pennsylvania, Octob er [16][17][18]1962.…”
Section: Introductionmentioning
confidence: 99%
“…It is seen that Ti rates intersect those of Ni at lower temperature, around 600°C, but exceed them substantially above 800°C. The other Ni studies shown, from Gulbransen and Andrew [22], Progar and Lewis [23], and Atkinson et al [24], bound the Kofstad values in some proximity, but exhibit noticeable offsets. There is thus some uncertainty as to which data set might represent the best comparison for baseline NiO growth kinetics.…”
Section: Comparative Arrhenius Behaviormentioning
confidence: 94%
“…N.A. [9] Ni (G) 1.63 9 10 6 4.52 9 10 -4 167 550-700 6 0.99 [22] Ni (P) 1.38 9 10 6 3.84 9 10 -4 174 815-1370 1-2 1.00 [23] Ni (A) 5.22 9 10 6 1.45 9 10 -3 154 500-800 109 0.98 [24] agreement with overall TiO 2 control. The diversion of the 500°C Ni49Ti data and the other Ni-Ti alloys at 135-150 kJ/mol suggests that there may be a common factor causing this deviation.…”
Section: Comparative Arrhenius Behaviormentioning
confidence: 99%
“…Although the kinetics of nickel oxidation have been widely studied [17][18], its interaction with PZT films has not been reported. In this work, PZT thin films were prepared by sol gel on two types of nickel, untextured and (200) textured foil, and the evolution of nickel oxide was Sol A + 10% w/v of PZT seeds with particle size lower than 100 nm [19], three layers, pre-annealed at 400 ~ for 10 seconds followed by rapid heating to 700 ~ annealed for 30 min, fast cooling.…”
Section: Introductionmentioning
confidence: 99%